Observational constraints on the survival of pristine stars. Issue 1 (2nd May 2019) - Magg, Mattis; Klessen, Ralf S; Glover, Simon C O; Li, Haining
Abstract: There is a longstanding discussion about whether low-mass stars can form from pristine gas in the early Universe. A particular point of interest is whether we can find surviving pristine stars from the first generation in our local neighbourhood. We present here a simple analytical estimate that puts tighter constraints on the existence of such stars. In the conventional picture, should these stars have formed in significant numbers and have preserved their pristine chemical composition until today, we should have found them already. With the presented method most current predictions for survivor counts larger than zero can be ruled out.